Competition of memory effect and thermal degradation on the crystallization behavior of polyphenylene sulfide. (2nd December 2022) - Hu, Sihao; Yang, Feng; Xiang, Ming; Cao, Ya; Wu, Tong; Fu, Qiang
Abstract: Polyphenylene sulfide (PPS) is one of most widely used special engineering plastics in the world. However, owing to the unique memory effect and thermal degradation effect, the crystalline structure of PPS is extremely difficult to control during the practical processing, resulting in the deterioration of processability and performance of PPS products. In this work, the differential scanning calorimetry (DSC), polarized optical microscopy (POM), in-situ X-ray diffraction (XRD), fourier transform infrared spectroscopy (FT-IR) and rheological tests were carried out to distinguish these two effects on the crystallization behavior of PPS systematically. It is found that the memory effect and thermal degradation compete "as one falls, another rises" on the crystallization behavior of PPS, both of which accelerate the crystallization rate and reduce the uniformity of crystalline structure. The residual of local ordered structures in PPS melt increases the nucleation rate significantly and could be eliminated as the pre-treatment temperature ( T p ) reaches 350 °C. Nevertheless, the chain scission reaction is activated and dominates the crystallization process of PPS when T p is higher than 350 °C, leading to the notable promotion of crystal growth rate. Accordingly, processing around the transition temperature can minimize the cooperation of melt memory and thermal degradation on the crystallization behavior of PPS, resulting in the lowest crystallization rate and the most uniform crystal size distribution. Graphical abstract: Diagram of competition of memory effect and thermal degradation on the crystallization behavior of PPS. Image 1 Highlights: Memory effect and thermal degradation occur inevitably of PPS. PPS has a unique crystallization behavior due to memory effect and chain scission. Both effects can be minimized at the pre-treatment temperature of 340–350 °C.